(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
Six samples of SBA-15 mesostructure were prepared. Process was proceeded with constant amount of TEOS, at different temperatures (70,100 and 130 Cº) using different amounts of P123 as structure directing agent (SDA). Results showed that both, the temperature of the hydrothermal treatment and the amount of (SDA) clearly affect on isothermal adsorption curves and the all pore structure factors. When the mass of SDA was 23 m.mol at different temperature (70,100,130 Cº) the specific surface area was 640,734 and 382 m2/g respectively. Where at constant temperature 100 Cº and different mass of SDA (23, 46, 69 m.mol ) the surface area was 734,852,832 m2/g respectively .The distribution of pore volume also was changed.